Android Based Learning Media for Dyscalculia Children at Nurul Jadid Islamic Boarding School - Moh Syadidul Itqan; Mida Rosida; Dini Melinda Ulfatul Azizah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
A conditions that are different from other Normal Children in terms of mental, physical, and social characteristics called Children with Special Needs. Dyscalculia is a term referring to a wide range of difficulties with mathematics, including weaknesses in understanding the meaning of numbers, and difficulty applying mathematical principles to solve problems. The difference in conditions with other normal children, required a different approach in Teaching and Learning Activities of the other Normal Children. One of these different approaches is to use mobile learning devices as an effective learning media for Children with Special Needs to realize the material presented by the Teacher. This research was carried out for the 2020/2021 Students at Junior High School of Nurul Jadid, Karang Anyar Paiton Probolinggo. The purpose of this research is to produce an android application to help Children with Special Needs learn. This research method is research and development. The result of this research is that an android application has been produced as an effective learning media for children with special needs.